Fibre - Video Education Australasia; Robyn, Holdsworth (Bendigo, Vic.: Video Education Australasia, 2022)
Looks at the much underplayed role fibre plays in our diet, and how fibre protects us from conditions like colon cancer, coronary heart diseases, diabetes, diverticulitis, high cholesterol and obesity. Also discusses the dietary recommendations for fib